Late Pleistocene plant macro-fossils from the Gokarna Formation of the Kathmandu Valley, Central Nepal - Bhandari, Sudarshan; Momohara, Arata; Paudayal, Khum N (Bulletin of the Department of Geology, 2009)
The Kathmandu Valley offers the best archive to study the Late Pleistocene climate in Nepal. The Gokarna Formation, constituting the middle part of the sedimentary sequence of the Kathmandu Valley comprises alternating layers of carbonaceous clay, silt, massive to parallel and large scale cross stratified, fine to coarse grained sands and occasional gravel layers, deposited at fluvio-deltaic and lacustrine environment. The organic rich layers of clay, silt, silty-sand and micaceous fine sand consists of abundant plant macro-fossils (fruit, seed and leaves). Plant macrofossils assemblage from the Gokarna Formation (thickness 28.5 m, Dhapasi section) in the northern part of the valley consists of 56 taxa from 35 families. Depending upon the available plant, seven macrofossil assemblages, DS-I to DS-VII in ascending order were established. The common tree and shrubs discovered from this section were Eurya, Ficus, Carpinus, Quercus, Alnus, Rubus, Pyracantha, Zizyphus, Carpinus, Boehmeria etc. Carex, Scirpus triqueter, Scirpus, Polygonum, Euphorbia, Oxalis, Mosla, Viola etc. were the common herbaceous taxa. The constant occurrence of subtropical and warm temperate taxa including Eurya, Ficus, Pyracantha and Zizyphus indicated that subtropical and warm temperate climate continued during the deposition of those macrofossil assemblages. However change in the constituents of those taxa and occurrence of taxa indicating cooler climatic condition like conifers and Betula may indicate minor fluctuation of climate during the deposition of the Gokarna Formation.   doi: 10.3126/bdg.v12i0.2252 Bulletin of the Department of Geology, Vol. 12, 2009, pp. 75-88